SOSIALISASI OLAHRAGA PICKLEBALL DI SMP - Kusnanda , Fan Dariel; Kahri , Ma’ruful; Haffyandi , Recky Ahmad (Universitas Hamzanwadi, 2024)
The purpose of pickleball socialization is to disseminate pickleball and provide an understanding of how to play pickleball correctly and to increase teenagers' awareness of the importance of exercising. Qualitative descriptive research method in the form of socialization. Students totaled 87 samples from classes VII to IX and 3 sports teachers. Socialization activities use random sampling techniques. The process is sorted into several stages, there are the preparation stage, the implementation stage and the evaluation stage. As a result, the implementation team found several positive responses from students that their desire to know pickleball is very high. It can be seen in the enthusiasm of students when following the entire series from the beginning to the end of the activity. It can be concluded that students or sports teachers already know in general about pickleball sports and are able to practice the basic techniques of playing pickleball and know the standard rules of pickleball sports correctly.